Efficacy of intralesional amphotericin B for the treatment of cutaneous leishmaniasis - Vahid Mashayekhi Goyonlo; Elham Vosoughi; Bita Kiafar; Yalda Nahidi; Akram Momenzadeh; Ahmad Reza Taheri (Wolters Kluwer Medknow Publications, 2014)
Background: Antimoniate compounds have been used as gold standard treatment for cutaneous leishmaniasis since many years ago, but with increase in incidence of drug as well as individual contraindications, more attention has been given to alternative treatments. Aim: The aim of this study was to evaluate the efficacy of intralesional amphotericin B as an alternative treatment for cutaneous leishmaniasis in Mashhad, Iran, during 2007-2009. Materials and Methods: Non-random sampling from both sexes and without any age limitation of cases eligible for this alternative treatment was done. Size and induration of lesions were measured before beginning and weakly during the treatment. Amphotericin B (2 mg/ml) was injected into lesions weekly for up to 12 weeks and the cases were followed up for the treatment responses, possible side effects and recurrence of the disease. Results: A total of 93 patients with a mean age of 20.81 ± 15.26 years were included in this study. At the end of 12 th week, 61.4% of the patients were recovered completely (more than 90% reduction in size and induration), 21.6% had partial remission (60-90% reduction in size and induration), and 17% had less than 60% reduction in size and induration of skin lesions. Injection side effects were insignificant and did not lead to premature discontinuation of treatment in any patients. Conclusion: Weekly intralesional injection of amphotericin B looks promising, considering the fact that most of the patients in this study were resistant to antimoniates.